Topseal integrity assessment using seal properties and leakage phenomena. (May 2022) - Foschi, M.; Van Rensbergen, P.
Abstract: We present a novel seismic interpretational workflow applied to a large gas-chimney located above the Marjoram Gas Field, offshore NW Borneo. The gas-chimney is hosted by a clay-dominated sealing sequence characterised by meter-scale silt beds. The sealing sequence is affected by a complex network of normal faults. The gas chimney, interpretable as vertical anomaly cluster, is composed of several discrete amplitude anomalies and is the result of gas leakage from the crest of a ∼500 m thick carbonate pinnacle-reef below. By analysing the seal properties and the anomalies composing the vertical anomaly cluster we argue that the leakage is consistent with migration of gas either along faults or using faults via cross-fault-plane juxtapositions. We show that this process is focussed within a narrow pathway rather than spread over the fault network. Mode I fault opening in response to the large capillary pressure exerted by the long gas column of the subjacent Marjoram Gas Field is postulated to be the cause of leakage. Highlights: The Marjoram Gas Field is a multi-trillion cubic feet reservoir obscured by a large gas chimney. Analysis of the gas chimney provides a precise pathway for gas leakage across the overburden. Leakage occur via mode I dilation of a fracture induced by the large gas column in the reservoir.